Potential role of ghrelin in neuroprotection and cognitive function: implications for diabetic cognitive impairment - Zhang,Yuhan; Zhang,Ruihua; Wang,Xin; Shi,Leilei; Zhu,Hongzhe; Liu,Jiping (PeerJ, 2025)
Ghrelin is a class of brain and intestinal peptides. It regulates food intake and body glucose levels and maintains cellular homeostasis. In recent years, research has revealed that ghrelin may positively impact learning and memory. Despite ghrelin’s multiple functions in the central nervous system, its use as a therapeutic agent for neurologic dysfunction remains unclear. Diabetic cognitive impairment (DCI) is a severe neurological complication of diabetes mellitus. Its incidence is increasing as a comorbidity in endocrinology and neurology. Additionally, it is a risk factor for Alzheimer’ s disease (AD). Ghrelin levels are altered in patients with diabetes mellitus combined with cognitive impairment. Furthermore, modulation of ghrelin levels improved cognitive function in rats with DCI. These findings suggest the potential therapeutic importance of ghrelin in the pathogenesis of DCI. This article presents a comprehensive review of the pathogenesis of DCI and its potential modulation by ghrelin and its mimics. Furthermore, this study elucidates the therapeutic prospects of ghrelin and its mimics for DCI, aiming to identify novel therapeutic targets and research avenues for the prevention and management of DCI in the future.
Keywords: Amyloid beta; Mitochondrial deficits; Synaptic dysfunction; Neuroprotection; Ghrelin; Diabetes cognitive impairment